ACCESS TO PUBLIC INFORMATION IN THE DIGITAL ERA: AN EVALUATIVE STUDY OF POLICIES AND IMPLEMENTATION PRACTICES - Fachriza Ariyadi; Syamsuri; Iskandar (Adisam Publisher, 2025)
The purpose of this research is to investigate the role of digital technology in promoting transparency, accountability, and public participation through the disclosure of information. The form of this research is descriptive, analytical, and critical. Therefore, the author can comprehensively explain how Public Information Access in the Digital Era: An Evaluative Study of Policies and Implementation Practices. In this study, the author optimally utilized two data sources related to the research, namely primary and secondary data sources. The results of this study show that the Public information access policy has progressed normatively, characterized by the presence of regulations such as the Public Information Disclosure Law (Law No. 14 of 2008) and various derivative rules that support the public's right to information. The use of digital technology by public institutions is increasingly widespread, primarily through official websites, social media, and digital services (e-government). However, the quality and consistency of implementation vary significantly between institutions and regions. The level of public information disclosure remains uneven, with some institutions tending to be passive or unproactive in delivering information periodically or in response to public requests. The main obstacles in the implementation of digital information disclosure include a lack of human resource capacity, weak digital infrastructure, and low digital awareness and literacy among officials and the public. Public participation has increased significantly in the digital age; however, it has not been matched by a prompt and accurate response from public institutions to public requests or criticisms. The mechanism for addressing complaints and resolving information disputes remains suboptimal, particularly at the regional level, resulting in the public's right to information often being partially fulfilled. Digital technology has great potential to support the democratization of information. Still, it requires a political commitment, institutional capacity building, and public education to ensure that access to information is genuinely practical, inclusive, and participatory.